Quantum wave packet study of N(2D) plus H2 reactive scattering - Gogtas, F; Bulut, N (Wiley, 2006)
N(D-2) + H-2 -> NH + H reaction at zero total angular momentum is studied by using a time dependent quantum wave packet method. State-to-state and state-to-all reactive scattering probabilities for a broad range of energy are calculated. The probabilities show many sharp peaks that ascribed to reactive scattering resonances. The probabilities for J > 0 are estimated by using the J-shifting method. The integral cross sections and thermal rate constants are then calculated. (c) 2005 Wiley Periodicals, Inc. Int J Quantum Chem 106: 833-838, 2006
Keywords: reaction dynamics; wave packet study; N+H-2; reactive scattering